2018
DOI: 10.1175/mwr-d-18-0021.1
|View full text |Cite
|
Sign up to set email alerts
|

The Unexpected Rapid Intensification of Tropical Cyclones in Moderate Vertical Wind Shear. Part II: Vortex Tilt

Abstract: We investigate a class of tropical cyclones (TCs) that undergo rapid intensification (RI) in moderate vertical wind shear through analysis of a series of idealized model simulations. Two key findings derived from observational analysis are that the average 200–850-hPa shear value is 7.5 m s−1 and that the TCs displayed coherent cloud structures, deemed tilt-modulated convective asymmetries (TCA), which feature pulses of deep convection with periods of between 4 and 8 h. Additionally, all of the TCs are embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 83 publications
(101 reference statements)
5
27
0
Order By: Relevance
“…Notice that the TC is located to the southern flank of the upper-level anticyclone. This pattern agrees well with the findings by Ryglicki et al (2018a) and Ryglicki et al (2018b). The authors pointed out that, the upper-level anticyclone generally creates moderate upper-level VWS, and TCs embedded in such environment likely have a potential to undergo RI.…”
Section: Upper-level Vwssupporting
confidence: 90%
See 2 more Smart Citations
“…Notice that the TC is located to the southern flank of the upper-level anticyclone. This pattern agrees well with the findings by Ryglicki et al (2018a) and Ryglicki et al (2018b). The authors pointed out that, the upper-level anticyclone generally creates moderate upper-level VWS, and TCs embedded in such environment likely have a potential to undergo RI.…”
Section: Upper-level Vwssupporting
confidence: 90%
“…With times, the most active convection moves anticlockwise, and approaches to east flank of the storm (Figure 5). This evolution feature bears many similarities as previous studies (Ryglicki et al, 2018a;Ryglicki et al, 2018b;Li et al, 2020), indicating that an inward-spiraling inner cloud band moves to upshear flank to form the eyewall cloud. This process agrees with Moon and Nolan (2010), in which they proposed a hypothesis that inner rainbands are simply convective clouds advected by the rapidly rotating TC wind, and then likely deformed into spiral shapes.…”
Section: Evolution Of Convective Asymmetriessupporting
confidence: 84%
See 1 more Smart Citation
“…Although the intensification mechanism involving localized, rotating convection is fundamentally three-dimensional and asymmetric, the evolution of axisymmetric tangential wind can still be usefully viewed in terms of the conventional axisymmetric view extended to include eddy fluxes of heat and momentum and unbalanced boundary layer processes (e.g., Smith et al 2009). The development of a deep, vertically aligned vortex, either through the reduction of tilt or the development of a vortex above (below) an existing low-level (midlevel) circulation center, facilitates symmetry and is thus a critical step in the intensification process (Dunkerton et al 2009;Wang et al 2012;Munsell et al 2017;Rios-Berrios et al 2018;Ryglicki et al 2018;Miyamoto and Nolan 2018;Chen et al 2018;Alvey et al 2020). This consideration is relevant for TCs at all stages in their early life cycle: from predepression up through tropical storm strength.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, deep vertical wind shear is capable of tilting the TC vortex, and this tilt has small-amplitude implications for TC motion (Flatau et al 1994). Previous studies have shown that the vertical profile of the environmental wind (e.g., helicity) is a determining factor in the TC vortex response to vertical wind shear (Onderlinde and Nolan 2016;Ryglicki et al 2018), and the resulting TC vortex structure controls the atmospheric layer responsible for steering the TC. Further, TC positions used to initialize model forecasts are imprecise, especially for weaker TCs without aircraft or land-based observations (e.g., Torn and Snyder 2012;Landsea and Franklin 2013).…”
Section: Introductionmentioning
confidence: 99%